Treatise on tolerance - Voltaire (Cambridge University Press, 2000)
The works presented in this volume, in a new English translation, are among the most important and characteristic texts of the Enlightenment, and bring together all three aspects of Voltaire: the writer, the doer and the philosophe. Originating in Voltaire's campaign to exonerate Jean Calas, they are works of polemical brilliance, informed by his deism and humanism and by Enlightenment values and ideals more generally. The issues that they raise, concerning questions of tolerance and human dignity, are still highly relevant to our own times.